Women and Public Procurement: A Review about ‘Feria Inclusiva’ Procedure - Singaucho Armas, Thalía Carolina (2025)
Gender-responsive public procurement have been established as a tool to contribute to the reduction of labor gaps and the economic empowerment of women, generating positive impacts. In 2022, the Ecuadorian Institute for Public Procurement (SERCOP) published the frst gender-responsive public procurement study, revealing that women participate in only 18.29% of the public market. In this context, it is essential to analyze the only procedure that explicitly included an element related to gender equality: the ‘Feria Inclusiva’ procedure. Through doctrine and complemented by a statistical analysis of the 2018-2021 period, this paper analyzes the participation of women in the ‘Feria Inclusiva’ procedure and its main characteristics linked to gender equality as an evaluation criterion. The main fndings suggest that gender gaps regarding management positions, amounts and volume of public contracts are smaller than the global trend. However, it would not be due to the application of the gender equality parameter, but rather it would be a collateral effect of the preferences applied to the smallest enterprises. The reduced incidence of the equality parameter in the awarding of contracts is also evident.